Fostering Organizational Justice and Agreeableness Predictors for Compliance Ethical Behavior - Sadia Anwar; Ashfaque Ali; Bahadur Ali Soomro, (Progressive Research Journal of Arts & Humanities (PRJAH), 2021)
Organizational justice’s role is highly identified in administrative distribution channels, restructuring, transfer of authority and responsibility, and staff inclusion into the decision-making process. This research investigates the impact of organizational justice and personality traits predictors in policy implementation that may significantly affect ethical behavior. In this crosssectional study, data are randomly collected from different public sector universities of Jamshoro, Sindh. A survey questionnaire is applied as the primary tool for data collection. The data is analyzed through SPSS version 26.0 for windows. The overall internal consistency among the items is 0.806, while the individual’s factors’ reliability was observed in satisfaction scores. The data were collected based on the 319 academic teaching faculty sample to apply correlation analysis and regression. Results explained that all three predictors, procedural, interpersonal, and agreeableness, are significantly related to ethical behavior; however, procedural justice is a stronger predictor of employees' ethical behavior. The outcomes of this research may be supportive for policymakers and practitioners to bring valuable insight for academic managers for the formation of future policies related to teaching staff in the Asian context, predominantly in Sindh, Pakistan.